Peningkatan Literasi Hijau Menuju Desa Wisata Muara Tiga Kecamatan Mulak Ulu - Sulastri, Sulastri; Adam, Mohamad; Saftiana, Yulia (Yumary: Jurnal Pengabdian kepada Masyarakat, 2024)
Purpose: Community services aim to enhance literacy in green tourist villages in Muara Tiga Village, Mulak Ulu Subdistrict, and Lahat Regency with a focus on rural economic development. Method: Community service activities were conducted in Muara Tiga Village, Mulak Ulu Subdistrict, Lahat Regency, involving the following steps: (1) identification of village issues and potential; (2) consultation with the subdistrict and village authorities regarding the community service plan; (3) socialization of community service activities in Muara Tiga Village, Mulak Ulu Subdistrict, and Lahat Regency; (4) Green Tourist Village Literacy Training; and (5) Empowering the community to develop the tourist village. Results/Findings: The community service activities, particularly the training on "green tourist village literacy," have improved knowledge and understanding of (1) tourist village concepts, (2) green tourist village concepts, (3) natural resources that can be utilized as tourist attractions, and (4) factors determining the success of tourist villages. Limitations: This study found that participants were not ready to understand literacy material because of their low level of education. Contribution: After participating in this training, the community developed the potential of the village to become a tourist village.